If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + -7x + 9 = 0 Reorder the terms: 9 + -7x + 3y = 0 Solving 9 + -7x + 3y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -7x + -9 + 3y = 0 + -9 Reorder the terms: 9 + -9 + -7x + 3y = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -7x + 3y = 0 + -9 -7x + 3y = 0 + -9 Combine like terms: 0 + -9 = -9 -7x + 3y = -9 Add '-3y' to each side of the equation. -7x + 3y + -3y = -9 + -3y Combine like terms: 3y + -3y = 0 -7x + 0 = -9 + -3y -7x = -9 + -3y Divide each side by '-7'. x = 1.285714286 + 0.4285714286y Simplifying x = 1.285714286 + 0.4285714286y
| (s)2(s+3)+(4s-5)=148 | | 5.5-x=(-4.5-x) | | 7y-7=6y+13 | | 18-4k=-10-k | | -14=2x+-24 | | (3k+4)x-(2k-6)y=-10 | | 4a-8=8a-(4a+8) | | 2n+18=3n+37 | | x^2-14x+360=0 | | -10(10n-9)+6(-5n+7)= | | 310=3x-8(8x+7) | | 2(x+1)-1=11 | | c=38.34+0.50 | | 5x-2(x-3)=4x+15 | | 11d-10=6d | | N-6n= | | 4m^2n+(-m^2n)=0 | | 4m^2n+(-m^2n)= | | 0.1*x+0.25(5x)=5.25 | | log=0.45 | | 0.85x=612 | | (6x-10)+(6x+10)=18 | | 5(7x+1)=5+2x | | 2(x-7)+3x-1=4x+3 | | 2x+x+9x=3+35+2-4 | | 87b+17b= | | 20x-5x+4=15x-4 | | 25t=25t+5 | | 3x-a=b+a | | -81r+73r= | | g(x)=x^2+22x+12 | | 8x+5=2x-5 |